2022
DOI: 10.1007/s13577-022-00843-w
|View full text |Cite
|
Sign up to set email alerts
|

Roles of RNA-binding proteins in neurological disorders, COVID-19, and cancer

Abstract: RNA-binding proteins (RBPs) have emerged as important players in multiple biological processes including transcription regulation, splicing, R-loop homeostasis, DNA rearrangement, miRNA function, biogenesis, and ribosome biogenesis. A large number of RBPs had already been identified by different approaches in various organisms and exhibited regulatory functions on RNAs’ fate. RBPs can either directly or indirectly interact with their target RNAs or mRNAs to assume a key biological function whose outcome may tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 158 publications
0
4
0
Order By: Relevance
“…Our results revealed that the GO biological process (BP) term RNA splicing was strongly associated with functions of these 11 common genes, indicating that this process is strongly linked to pathogenic mechanisms of both COVID-19 and PTB. Notably, viruses like SARS-CoV-2 manipulate host splicing to bolster replication [ [15] , [16] , [17] ], while in PTB, splicing plays regulatory roles in both the host immune response and pathogen survival [ 18 , 19 ]. Therefore, targeting of splicing factors may impede viral or bacterial replication and enhance immune responses.…”
Section: Discussionmentioning
confidence: 99%
“…Our results revealed that the GO biological process (BP) term RNA splicing was strongly associated with functions of these 11 common genes, indicating that this process is strongly linked to pathogenic mechanisms of both COVID-19 and PTB. Notably, viruses like SARS-CoV-2 manipulate host splicing to bolster replication [ [15] , [16] , [17] ], while in PTB, splicing plays regulatory roles in both the host immune response and pathogen survival [ 18 , 19 ]. Therefore, targeting of splicing factors may impede viral or bacterial replication and enhance immune responses.…”
Section: Discussionmentioning
confidence: 99%
“…RBPs are particularly relevant in the nervous system, where they regulate critical aspects of neurogenesis, neuronal function, and nervous system development (4,5). Alterations in RBP expression and function are linked to neurological disorders, neurodegenerative diseases, and brain tumor development (6)(7)(8)(9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…In the nucleus, some RNA-binding proteins (RBP) often function as AS regulators in a particular way in the disease course [ 13 , 14 ]. Functional disruptions in RBPs may be a major cause or consequence of a disease [ 15 , 16 ]. CUGBP Elav-like family (CELF) and muscleblind-like (MBNL) proteins are some examples of RBPs functioning as splicing regulators; they play vital roles in myotonic dystrophy by promoting opposite effects on the splice site or exon usage, affecting mRNA localization and stability in the cytoplasm [ 17 ].…”
Section: Introductionmentioning
confidence: 99%